(untitled) (Journal of Current and Advance Medical Research, 2023)
Background: High-sensitive C-reactive protein (hs-CRP) is a marker of inflammation. CRP may play a significant role as a predictor of inflammation in nephropathy and chronic kidney disease. Objective: The aim of the present study was to estimate hs-CRP levels and serum creatinine levels among type 2 diabetes mellitus patients and to determine association between them. Methodology: This was an analytical, quantitative, hospital-based study performed on type 2 diabetic patients and was conducted at the Department of Biochemistry of BIRDEM General Hospital, Dhaka, Bangladesh. It was analyzed serum concentrations of hs-CRP, serum creatinine, serum glucose and family history of the patients. Results: This observational study showed that a greater number of diabetics had high serum creatinine level (41% vs 59%). 67.6% of study population had moderate to high level of hsCRP. hs-CRP was found significantly higher in diabetics with renal impairment (1.66±0.86 vs. 7.01±3.44, p<0.001). Serum creatinine had positive (r=0.88, p<0.001) correlation with hs-CRP. Glycated hemoglobin and serum creatinine were linearly related with inflammatory marker. When creatinine increased by 1 unit, hs-CRP increased by 0.84 units (β=0.84, p=<0.001). Conclusion: This study concludes that the increase in serum hs-CRP value type 2 diabetic patients increase the risk of diabetic nephropathy and thus increase the value of serum creatinine level. Journal of Current and Advance Medical Research, July 2022;9(2):59-62